Causalidad e imputación en la responsabilidad civil médica por infracción al deber de información en intervenciones médicas riesgosas - Ugarte Mostajo, Daniel (2024)
This paper addresses the problem of determining causation between a doctor’s breach of his duty to inform and injuries suffered by the patient as a consequence of the occurrence of uninformed risks. The paper criticizes the application of “hypothetical causality” as an explanatory figure for the causal link and also criticizes the idea of ‘hypothetical informed consent’ as a mechanism to exempt the liability of the defaulting doctor. Finally, the paper argues that the real problem in such case scenarios is not strictly a causation one, yet it has a normative and prudential nature. Accordingly, the solution does not require to establish a patient’s supposed a consent, but to correctly apply objective and subjective attribution criteria.